The 2019 Indonesian Presidential Election: Propaganda in Post-Truth Era - Akhirul Aminulloh; Myrtati Dyah Artaria; Yuyun Wahyu Izzati Surya; Kamil Zajaczkowski (Nyimak: Journal of Communication, 2021)
Presidential elections often are colored by propaganda and post-truth politics in its campaign to influence public opinion. This study aimed to identify the way and forms of propaganda and post-truth communicate political messages from the 2019 presidential election in Indonesia through political communication on social media. This research employed a mixed-methods approach that combines quantitative and qualitative methods. The quantitative data were obtained from Twitter with social network analysis (SNA) from December 2018 to March 2019. Meanwhile, the qualitative data were obtained from literature searches and expert interviews. The results of this analysis indicated that presidential candidate Jokowi was widely rumored to be a liar, claimant of success, weak leader, communist, pro-China, and anti-Islam. There were also many rumors that referred to presidential candidate Prabowo as a pro caliphate, human rights violator, person with a questionable religion, bad-tempered person, inexperienced leader, and hoax spreader. These negative issues constitute propaganda in the form of stories, rumors, and myths that were manipulated to influence public opinion on social media. Some parts of society believed them based on emotional belief instead of on rationally observed facts. We conclude that even when it involves many people in a big nation, propaganda can be manipulated to influence public opinion.Keywords: Propaganda, post-truth, social media, political communication, presidential election ABSTRAKPemilihan presiden sering kali diwarnai oleh propaganda dan politik pasca-kebenaran dalam kampanyenya untuk memengaruhi opini publik. Kami mempelajari kasus pemilihan presiden di Indonesia tahun 2019. Penelitian ini bertujuan untuk mengidentifikasi bagaimana bentuk-bentuk propaganda dan post-truth mengkomunikasikan pesan politik melalui komunikasi politik di media sosial. Penelitian ini menggunakan pendekatan metode campuran, yaitu kombinasi metode kuantitatif dan kualitatif. Data kuantitatif diperoleh dari media sosial Twitter dengan analisis jejaring sosial (SNA) dari Desember 2018 hingga Maret 2019. Data kualitatif diperoleh dari penelusuran literatur dan wawancara ahli. Hasil analisis menunjukkan bahwa capres Jokowi banyak diisukan sebagai pembohong, klaim keberhasilan, pemimpin lemah, komunis, pro-China, dan anti-Islam. Banyak rumor yang menyebut calon presiden Prabowo sebagai pro khilafah, pelanggar HAM, orang yang agamanya dipertanyakan, pemarah, pemimpin yang tidak berpengalaman, dan penyebar hoax. Implikasi dari penelitian ini adalah bahwa isu-isu negatif tersebut merupakan propaganda berupa cerita, rumor, dan mitos yang dimanipulasi untuk memengaruhi opini publik di media sosial. Sebagian masyarakat percaya bahwa propaganda ini sebagai kebenaran karena didasarkan pada keyakinan emosional, bukan fakta yang diamati secara rasional. Kami menyimpulkan bahwa meskipun melibatkan banyak orang di negara besar, propaganda dapat dimanipulasi untuk memengaruhi opini publik.Kata Kunci: Propaganda, post-truth, media sosial, komunikasi politik, pemilihan presiden